(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Peoples are, undoubtedly the best sources of an organization.Sourcing the best people from the industry has become the top most priority ofthe organizations today. In such a competitive scenario, talent management hasbecome the key strategy to identify and filling the skill gap in a company byrecruiting the high worth individuals from the industry. It is a never endingprocess that stars from targeting people. Talent management is responsible formaintaining the balance between entry and exit of talented people in anorganization. The key to talent management understands the individualmotivations, drives, and aptitudes of the person with the talent. Too manytimes management makes a huge mistake in assuming that since they are talentedand have been promoted to a management position that the person they manage ismotivated and driven by the same as they. But is not the case. This paper is anattempt to study the various factors responsible for managing talent and itsneed in an organization